La ley de contrataciones del Estado Peruano y su eficiencia en los procesos de selección y contratación en la municipalidad provincial Sánchez Carrión - Huamachuco 2015 - 2016 - Vera Paredes, Julissa Jovana (2016)
The present research work has like main objective determinate the degree of effectiveness of the Law of Trading of the Peruvian State in the selection and trading processes in the Sanchez Carrion Provincial Municipality – Huamachuco 2015 – 2016. With the finality of demonstrate the importance of the correct application of the law, the information was compiled through the interviews addressed to employees of the Provincial Municipality with regard to the validity of the new law of trading of the state, in that way surveys addressed to permanent administrative personal of the Provincial Municipality were applied. The structure of the work included since the Problematic Reality, Antecedents, Justification, Formulation of the Problem, Theoretical Support, Formulation of Hypothesis, Methodology, Techniques, Results, Discussion, Conclusions and wide source of information of different specialties, who with their contributions helped to clarify the problematic in reference and helped to contrast the raised hypothesis expressed of the following way: “the efficient fulfillment of the law of trading of the Peruvian will improve State in the selection and trading processes in the Sanchez Carrion Provincial Municipality – Huamachuco 2015 – 2016. Finally, this research study will provide a most information to the Sanchez Carrion Provincial Municipality – Huamachuco about the new Law of Trading of the Peruvian State and its Regulations in force, through its conclusions and recommendations.